The effect of language dominance on radical awareness and statistical learning in Singaporean Chinese bilinguals - Tan, Jun Yi (Nanyang Technological University, 2020)
This study examined the effect of language dominance on Chinese radical awareness and visual statistical learning abilities in Singaporean Chinese-English bilinguals. Language dominance was assessed using a self-report measure of language history, use, proficiency and attitudes. Chinese radical awareness was assessed using a picture naming task, which examined radical sensitivity, as well as an odd-one-out task, which assessed radical recognition. Statistical learning was assessed using visually presented stimuli within a triplet learning paradigm. Thirty-six healthy Singaporean Chinese bilinguals (M = 26.1, SD = 4.14) were split into two even groups, consisting of participants who were More English-Dominant (MED) and participants who were Less English-Dominant (LED). Independent samples t-tests identified a statistically significant effect of language dominance on visual statistical learning accuracy (p = .03, d = .66) and radical sensitivity (p = .04, d = .63). MED participants were found to have significantly higher visual statistical learning accuracy but lower Chinese radical sensitivity and recognition accuracy, as compared to LED participants. These results seem to suggest an effect of L1 language dominance on language processing in Singaporean bilinguals. Findings of this study can be used to establish a more comprehensive research base for understanding bilingual lexical access in visual word recognition.